Biotin and glucose co-modified multi-targeting liposomes for efficient delivery of chemotherapeutics for the treatment of glioma. (1st January 2021) - Liu, Qijun; Zhou, Lin; Lu, Runxin; Yang, Chunyan; Wang, Siqi; Hai, Li; Wu, Yong
Graphical abstract: Abstract: Glioma is one of the most common primary intracranial tumor, but the current treatments of glioma are far from satisfying. As the major treatment option for malignant glioma, chemotherapy has its own disadvantages, including low chemotherapeutic agents delivery across blood–brain barrier (BBB) and lack of specificity. Therefore, new approach permitting glioma targeting ability that can allow an efficient therapeutic delivery into the glioma regions is urgently required. Ligand-mediated liposomes have shown great potential for improving the efficiency of glioma treatment. In our study, the multi-targeting liposomes based on glucose and biotin were constructed for the first time. We synthesized two ligands (Glu3 -Chol, Bio2 -Chol), prepared three types of modified liposomes (Glu3 -Lip, Bio2 -Lip and Bio2 + Glu3 -Lip) and evaluated the glioma-targeting ability of these liposomes which were using paclitaxel (PTX) as the model drug in vitro. Besides, the uptake mechanism of Bio2 + Glu3 -Lip was investigated. PTX-loaded Bio2 + Glu3 -Lip (PTX-Bio2 + Glu3 -Lip) exhibited satisfactory targeting effect in Bend.3 and C6 cells in vitro, in which the cellular uptake of Bio2 + Glu3 -Lip were 4.04- and 3.49-fold more than that of the uncoated liposomes (Lip). The results suggested the multi-targeting liposomes (Bio2 + Glu3 -Lip) is a promising formulation for glioma, which was almost consistent with the results of in vivo imaging. In summary, we have designed and fabricated an effective delivery system to treat glioma.